What Anyone Can Know The Privacy Risks of Social Networking Sites. - Rosenblum, D. (IEEE Security and privacy : building confidence in a networked world)
For the Net generation, social networking sites have become the preferred forum for social interactions, from posturing and role playing to simply sounding off. However, because such forums are relatively easy to access, posted content can be reviewed by anyone with an interest in the users' personal information.